Accurate graphene-based absorber for slight leakage detection of Radon and chloroform air-pollution - Bahareh Khodadadi; Pejman Rezaei; Soheil Hadipour (Results in Physics)
Metamaterial absorbers, particularly those tailored for the terahertz (THz) spectrum, are increasingly capturing the attention of engineers and researchers around the globe due to their potential applications in advanced sensing and imaging technologies. This paper presents a comprehensive study of a novel tunable terahertz metamaterial perfect absorber demonstrating remarkable capabilities, making it particularly suitable for various sensing applications. One of the standout features of this design is its high sensitivity to changes in refractive indices. This characteristic is crucial for precise gas detection, which is becoming increasingly important across various fields, including environmental monitoring, industrial safety, and biomedical diagnostics. The ability to accurately identify gases can facilitate early detection of hazards and improve health outcomes. The proposed metamaterial absorber comprises three distinct layers: a gold layer, a silicon dioxide (SiO2) layer, and a graphene layer. As a result, this design structure achieves a perfect absorptivity at 12.99 THz, which boasts a Q-factor of 14.94, which reflects its quality and efficiency in resonating at the desired frequency.The advancements detailed in this paper hold notable promise for enhancing gas detection technologies, potentially paving the way for innovative solutions in both industrial applications—such as monitoring emissions and detecting leaks—and biomedical contexts. The findings presented here could lay the groundwork for future research and development.